AKHLAK KEPADA ALLAH SWT - Muhrin, Muhrin (UIN Antasari Banjarmasin, 2021)
ABSTRACTIslamic teachings that are universal in nature must be applied in everyday life both in society, nation and state in totality. The application is certainly related to the implementation of one's rights and obligations to God, His apostles, fellow human beings, and the surrounding environment. Especially the application of a servant's morals to His Lord will be seen from the knowledge, behavior, and lifestyle that are filled with awareness of monotheism to Allah SWT. This can be proven by various righteous deeds, piety, and obedience to Allah SWT. Likewise, proof of love for the Prophet Muhammad such as by implementing the sunnah, mutual respect for fellow human beings, and preserving the natural environment. For this reason, in managing life, norms and values are needed to measure standards to determine whether the actions and actions chosen are good or not, right or wrong, so that what is seen is not only self-interest, but also the interests of others, common interests, the interests of the community. humanity as a whole. Thus, each individual is required to have good morals or morality.KEYWORDS: Morals; Islamic Teachings; Allah Swt. ABSTRAKAjaran Islam yang bersifat universal harus dapat diterapkan dalam kehidupan sehari-hari baik bermasyarakat, berbangsa dan bernegara secara totalitas. Penerapan tersebut tentu berhubungan dengan pelaksanaan hak dan kewajiban seseorang kepada Tuhan, rasul-Nya, sesama manusia, dan lingkungan di sekitarnya. Khusus penerapan akhlak seorang hamba kepada Tuhan-Nya akan terlihat dari pengetahuan, perilaku, dan gaya hidup yang dipenuhi dengan kesadaran tauhid kepada Allah Swt. Hal itu bisa dibuktikan dengan berbagai perbuatan amal shaleh, ketakwaan, dan ketaatan kepada Allah Swt. Begitu juga bukti kecintaan kepada Rasulullah saw seperti dengan melaksanakan sunnah, saling menghormati sesama manusia, dan menjaga kelestarian lingkungan alam. Untuk itu, dalam menata kehidupan diperlukan norma dan nilai diperlukan standar ukuran untuk menentukan apakah perbuatan dan tindakan yang dipilih itu baik atau tidak, benar atau salah, sehingga yang dilihat bukan hanya kepentingan diri sendiri, melainkan juga kepentingan orang lain, kepentingan bersama, kepentingan umat manusia secara keseluruhan. Dengan demikian setiap individu dituntut untuk memiliki moral yang baik atau akhlakul karimah.KATA KUNCI: Akhlak; Ajaran Islam; Allah Swt.